The mechanism of ORFH79 suppression with the artificial restorer fertility gene Mt‐GRP162. Issue 1 (7th May 2013) - Hu, Jun; Huang, Wenchao; Huang, Qi; Qin, Xiaojian; Dan, Zhiwu; Yao, Guoxin; Zhu, Renshan; Zhu, Yingguo
Summary: The restoration fertility complex (RFC) was previously identified in Honglian (HL)‐cytoplasmic male sterility (CMS) rice ( Oryza sativa ), and glycine‐rich protein 162 (GRP162) is responsible for binding to the CMS‐associated transcript atp6‐orfH79 . Here, we engineered a recombinant GRP162 containing the mitochondrial transit peptide, termed Mt‐GRP162, as an artificial restorer of fertility ( Rf ) gene. Mt‐GRP162 was confirmed to bind to CMS‐associated RNA and to localize to the mitochondria. The transgenic plants showed restored fertility with partially functional pollen. We found that the expression of ORFH79 decreased in transgenic plants, while the expression of atp6‐orfH79 was not changed. These findings indicate that Mt‐GRP162 restores fertility by suppressing the expression of the cytotoxic protein ORFH79 at the post‐transcriptional level rather than via the cleavage of atp6‐orfH79 in the presence of RFC. These findings contribute to our understanding of the mechanisms of restoration through diverse pathways.